2020
DOI: 10.1002/cnm.3303
|View full text |Cite
|
Sign up to set email alerts
|

Deep learning for prediction of cardiac indices from photoplethysmographic waveform: A virtual database approach

Abstract: Deep learning methods combined with large datasets have recently shown significant progress in solving several medical tasks. However, collecting and annotating large datasets can be a very cumbersome and expensive task. We tackle these problems with a virtual database approach where training data is generated using computer simulations of related phenomena. Specifically, we concentrate on the following problem: can cardiovascular indices such as aortic elasticity, diastolic and systolic blood pressures, and b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 65 publications
0
11
0
Order By: Relevance
“… 2019 ; Huttunen et al. 2019 ). Two key components are required to build such realistic models, a validated one-dimensional haemodynamic model and realistic arterial networks based on anthropometric and haemodynamic parameters to represent a reliable human cohort.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“… 2019 ; Huttunen et al. 2019 ). Two key components are required to build such realistic models, a validated one-dimensional haemodynamic model and realistic arterial networks based on anthropometric and haemodynamic parameters to represent a reliable human cohort.…”
Section: Methodsmentioning
confidence: 99%
“…The objective of virtual patient generation for a cardiovascular system is to build a numerical model for blood flow that closely resembles a human patient in terms of blood flow parameters and vascular network. Previous research in virtual patient database generation methods can be found in references (Willemet et al 2015;Charlton et al 2019;Huttunen et al 2019). Two key components are required to build such realistic models, a validated one-dimensional haemodynamic model and realistic arterial networks based on anthropometric and haemodynamic parameters to represent a reliable human cohort.…”
Section: Virtual Patient Databasementioning
confidence: 99%
“…Yet, the in-silico data allow us for performing an initial validation of the proposed methodology, whose results will allow to proceed with the clinical validation. Previous works have used a similar approach to validate ML-based techniques using virtual patients when real clinical data were not available ( Huttunen et al, 2019 ; Bikia et al, 2020b , 2021 ; Huttunen et al, 2020 ). Hence, the present study proposes the methodology rather than the model per se .…”
Section: Discussionmentioning
confidence: 99%
“…They have provided a valuable alternative for the assessment of pressure and flow in the entire arterial network providing additional pathophysiological insights, which are difficult to acquire in-vivo. Numerous previous studies have used in-silico data for the estimation of aortic BP, cardiac output, aortic PWV and many more [56][57][58][59][60] . Importantly, in-silico studies allow for the preliminary evaluation of predictive models across a wide range of cardiovascular parameters 61 in a quick and cost-efficient way, while their results can be rather informative of the design of clinical studies 62,63 .…”
Section: Discussionmentioning
confidence: 99%